Standard ecological and molecular research methods and techniques for Labyrinthula spp. - Sullivan, Brooke K.; Martin, Daniel L.; Yoshioka, Reyn M.; Brakel, Janina; Jakobsson-Thor, Stina; Eisenlord, Morgan; Trevathan-Tackett, Stacey M. (Frontiers in Marine Science, 2023)
Labyrinthula are unicellular protists occupying diverse spatial and functional niches, including various roles in host and ecological function, fatty acid production, pandemic marine disease and saprobic decomposition. Labyrinthula species span tropical and temperate climates and have been isolated from each marine coastal ecosystem tested. Our understanding of primary cellular and molecular functions of Labyrinthula has substantially progressed through a combination of increased global investments, research interest and technological advances. Recent advances in molecular techniques provide a toolkit for advancing ecological questions in marine infectious disease in seagrass meadows around the world. Here we provide a comprehensive review of relevant ecological and molecular techniques used in long-term research and the progression of Labyrinthula scholarship. Our aims in preparing this review are to: 1) share, compare and advance global Labyrinthula protocols, 2) increase accessibility to robust methodology to encourage the uptake of Labyrinthula-based questions into marine studies of molecular and ecological qualities of Labyrinthula and 3) encourage uptake of robust Labyrinthula-based questions into coastal marine studies, while also encouraging international collaborative networks across multiple fields. Lastly, we discuss gaps in the over 100 years of Labyrinthula research and opportunities for expanding research on this model marine organism.